Excel VBA programming : the complete guide - Paskhaver, Boris ([Packt Publishing], 2019)
"Welcome to Excel VBA Programming-The Complete Guide, the most comprehensive VBA course! Visual Basic for Applications (VBA) is a powerful language built on top of popular Microsoft Office applications such as Excel, Access, and Outlook. It allows developers to write procedures called macros that perform automated actions. Anything that you can do in Excel, you can automate with VBA! No programming experience is required; complete beginners are more than welcome! VBA is a great language to start with because it lets you master the fundamentals of programming in a familiar work environment. No extra software is necessary: VBA is bundled with all modern versions of Excel. Excel is the world's most popular spreadsheet software and is available on over 750 million computers worldwide. Whether you use it for professional or personal reasons, VBA can help you remove redundancy in your workflows and accelerates your productivity drastically!"--Resource description page